Six Sigma Strategy in Continuous Improvement of the Supply Chain: A Bibliometric Study - Paraquett, Raissa; Senna, Pedro; Gomes dos Santos, Ana Carla Souza (Journal of Sustainable Competitive Intelligence, 2023)
Purpose: The objective of this scientific article is to conduct a bibliometric study on the Six Sigma strategy applied to the supply chain seeking to investigate how Six Sigma has been applied in mitigating risks in supply chains. For this, the main characteristics of the implementation of the methodology and its results in terms of reducing waste, errors and improving quality were analyzed. Methodology/approach: This study identified that the Six Sigma methodology can be used to minimize risks that may affect the entire supply chain, as well as strengthen a company's competitive position, allowing it to offer higher quality products and services, with competitive prices and greater efficiency. Originality/Relevance: They reside in the fact that the adoption of a strategic approach is fundamental for the successful implementation of the Six Sigma methodology in the supply chain. In addition, information management is essential for a successful implementation of the strategy and innovation management can help identify new opportunities for improvement and cost reduction in the supply chain. Key findings: This study presents a significant contribution to the literature on the application of the Six Sigma methodology in the supply chain, providing valuable insights for managers and researchers interested in improving the efficiency and quality of their companies' supply chain. Theoretical/methodological contributions: The theoretical contribution is a bibliometric analysis on the implementation of the Six Sigma strategy in the supply chain, highlighting the main strategies of this application and their impacts on supply chain management.